Organizational factors, organizational culture, job satisfaction and entrepreneurial orientation in public administration - Karyotakis, Konstantinos M.; Moustakis, Vassilis S. (The European Journal of Applied Economics, 2016)
The present paper outlines the critical role and influence of organizational culture and job satisfaction on the relationship between organizational factors and entrepreneurial orientation (EO) in the public sector through generating the theoretical framework. Upon examining these terms, a model that reflects their mutual relationships has been suggested. The amalgam of internal work environment, work discretion and rewards/recognition in combination with the appropriate degree of organizational boundaries, such as formalization, centralization, technology routines and connectedness, are crucial for fostering organizational culture and job satisfaction that lead to EO through innovativeness, proactiveness and risk taking.